ON THE ISSUE OF REPRESENTTION OF WATER/ECONOMIC JOURNALS IN THE SCIENTIFIC CITATION BASES - Natalia A. Valek (Водное хозяйство России: проблемы, технологии, управление)
The article presents the results of the analysis of the water/economic journals bibliometric data in leading bases of scientific citation (Russian Index of Scientific Citation (RISC), Web of Science Core Collection, and Scopus). We have analyzed the outcomes of the Clarivate Analytics – «Research Fronts 2020» and «Research Fronts 2020: active fields, leading countries» reports and based on them we have found out top issues of researches in the area of water/economic activities and leading countries involved in their development. According to editions rating in RISC, Web of Science, Scopus we have accessed scientific potential of Russian journals dealing with water/economic themes and have identified their place in the world rating. We have emphasized the problem of small quantity of the appropriated national editions in the world information researches’ flow. The undertaken research was targeted to studying of contemporary trends of the world water science and the practice of their reflection in scientific literature. We have propose some ways of enhancing the world-wide significance of the Russian relevant editions.